Vertebral Osteomyelitis Caused by Helicobacter cinaedi - Yoshizaki, Aisa (J Clin Microbiol, 2015)
Helicobacter cinaedi causes bacteremia, cellulitis, and gastroenteritis. We report the first case of vertebral osteomyelitis caused by H. cinaedi in an elderly man with low back pain and fever. The pathogen was detected in blood and lumbar disc, and the infection was successfully treated with oral doxycycline for 11 weeks.